The Characteristics and Outcomes of Patients Transported by Ambulance Due to Ambulatory Care Sensitive Condition: A Population-Based Descriptive Study in Osaka, Japan - Katayama, Yusuke; Kanehara, Atsushi; Yamashita, Yuya; Kitamura, Tetsuhisa; Oda, Jun (Frontiers in Public Health, 2022)
Background Ambulatory care sensitive conditions (ACSCs) are defined as clinical conditions for which the risk of emergency hospital admission can be reduced by timely and effective ambulatory care. However, the actual status of patients with ACSCs who are transported by ambulance and their outcomes have not been fully elucidated. The purpose of this study was to reveal characteristics and outcomes of patients with ACSCs who were transported by ambulance using population-based registry data in Osaka, Japan. Methods This descriptive epidemiological study was conducted in the 5-year period from January 2016 to December 2020, and included patients who were transported by ambulance due to sudden illness. In this study, ACSC was further classified into acute ACSCs, chronic ACSCs, and preventable ACSCs based on the ICD-10. The number of patients transported by ambulance for ACSCs per 100,000 population in each age group was calculated for each year. In addition, Poisson regression models were used to assess the trend in the number of ACSCs patients transported by ambulance. Results A total of 1,572,152 patients were included in this study (acute ACSCs, n = 69,621; chronic ACSCs, n = 12,250; preventable ACSCs, n = 96,036; and non-ACSCs, n = 1,394,245). The overall median age was 71 years (95% confidence interval [CI], 46-92). Patients with acute ACSCs (median age: 76 years [IQR: 60-84]) and chronic ACSCs (median age: 80 years [IQR: 72-87]) were older, while patients with preventable ACSCs were younger (median age: 66 years [95%CI: 3-81]) and included a high proportion of children (33.3%, 32,002/96,036). Regarding the outcome after treatment at the emergency department, 42.6% (670,392/1,572.152) of patients were hospitalized, while 82.3% (10,079/12,250) of patients with chronic ACSCs were hospitalized. No change was observed in adults (P = 0.001) or elderly (age ≥65 years) individuals (P = 0.376) with preventable ACSCs, however, among children, the number increased until 2019 (732.5) and then decreased in 2020 (371.8) (P = 0.392). Conclusion In this study, patients with chronic ACSCs were predominantly elderly, while patients with preventable ACSCs were polarized between children and the elderly. Among patients with preventable ACSCs, there was no change over time in adults and children, but there was a marked decrease among the elderly after 2020.